Novel Non-Steroidal Facial Cream Demonstrates Antifungal and Anti-Inflammatory Properties in Ex Vivo Model for Seborrheic Dermatitis - Corinne Granger; Anna Balato; Felipe Goñi-; Aurora Garre; Mridvika Narda (Adis, Springer Healthcare, 2019)
Abstract Introduction Seborrheic dermatitis (SEBD) is a chronic, recurrent skin disorder that typically occurs as an inflammatory response to fungi of the genus Malassezia. The development of an ex vivo model that mimics the fungal proliferation and skin inflammation of SEBD would play an important role in screening formulations for their efficacy in treating SEBD. Methods An ex vivo model for SEBD using human skin explants that had been mechanically manipulated to facilitate colonization of Malassezia furfur was developed. This model was used to evaluate the efficacy of a novel non-steroidal facial cream (NSFC) in inhibiting M. furfur proliferation and reducing inflammatory cytokine levels. Results This model reproduced some of the key pathological features of SEBD, including M. furfur proliferation and inflammatory cytokine production. Topical application of NSFC facial cream reduced M. furfur counts by 92% (p < 0.05) and levels of interleukin 8 (IL-8) and tumor necrosis factor alpha (TNF-α) by 82% and 40%, respectively (p < 0.05, both). Conclusion The proposed ex vivo model for SEBD could be a useful tool to evaluate topical antifungal treatments. The novel NSFC tested in this study reduced M. furfur proliferation and inflammatory cytokine levels following topical application and may be helpful in the management of SEBD. Funding ISDIN.